Identification and epidemiology of a novel Hepacivirus in domestic ducks in Hunan province, China - Chen, Jin-Tao; Chen, Kang-Jing; Wu, Kang-Wei; Yi, Shan-Hong; Shao, Jian-Wei (Frontiers in Veterinary Science, 2024)
The genus Hepacivirus comprises a diverse range of genetically distinct viruses that infect both mammalian and non-mammalian hosts, with some posing significant risks to human and animal health. Members of the genus Hepacivirus are typically classified into fourteen species (Hepacivirus A-N), with ongoing discoveries of novel hepaciviruses like Hepacivirus P and Hepacivirus Q. In this study, a novel hepacivirus was identified in duck liver samples collected from live poultry markets in Hunan province, China, using unbiased high-throughput sequencing and meta-transcriptomic analysis. Through sequence comparison and phylogenetic analysis, it was determined that this newly discovered hepacivirus belongs to a new subspecies of Hepacivirus Q. Moreover, molecular screening revealed the widespread circulation of this novel virus among duck populations in various regions of Hunan province, with an overall prevalence of 13.3%. These findings significantly enhence our understanding of the genetic diversity and evolution of hepaciviruses, emphasizing the presence of genetically diverse hepaciviruses duck populations in China. Given the broad geographical distribution and relatively high positive rate, further investigations are essential to explore any potential associations between Hepacivirus Q and duck-related diseases.